Investigating Tiling Decorations Ofsafavid Period, A Case Study Sheikh Lotfollah Mosque Of Isfahan - Sobouti, Hooman; Ebadei, Hamed (The Turkish Online Journal of Design Art and Communication, 2016)
Safavids were the true heirs of the magnificent art of Timurid period. In fact tiling art reaches the peak of its prosperity in Safavid era. An important reason for the flourishing of tiling art in this period is Shah Abbas’s interest in tile work and embellishment of mosques and holy shrines of Imams with tiling decorations. One of the most elegant monuments of Isfahan which catches the eyes of every viewer is Sheikh Lotfollah mosque. The significance of this building is due to its architecture which is imbued with talent and artistic excellence, thus elevating its worth. In the present article conducted by descriptive analytical method, the zenith of tile work, application of arabesque lines along with the unmatched masterpiece of the period; that is Sheikh Lotfollah mosque will be discussed.
Keywords: The Safavid; tiling art; Sheikh Lotfollah mosque